Stored seeds crambe (Crambe abyssinica Hochst) as affected by priming - Rocha, Vívian Palheta da; Santos, Lucas Antonio de Freitas; Silva, Ludmila Fonseca da; Santos, Luiz Antônio Silva dos; Rossetto, Claudia Antonia Vieira (Scientia Agraria Paranaensis, 2017)
The crambe (Crambe abyssinica Hochst) has been grown mainly due to their potential for oil production in their seed and as fodder plant. For this species, the high oil content impairs the storage potential of the seeds as well as the use of seeds in the presence of pericarp of the fruit at the time of sowing and the low availability of water in the soil may provide uneven germination. To facilitate the performance of the seeds can be used the seed priming techniques. The objective of this research was to evaluate the effect of different priming techniques in physiological quality of crambe seeds stored under controlled conditions. Therefore, the experiment was conducted in the period 2015-2016 using classified seeds, processed and packed in paper bags. After zero, three and six months of storage, the seeds were submitted to unmonitored hydration techniques (immersion in water), matriosmopriming with PEG 6000 -0.2 MPa, moist atmosphere, matripriming and unconditioned seeds were used as control. Later, the seeds were dried and evaluated by germination and vigor tests (first count, seedling performance, seedling emergence and electrical conductivity). From the results, it can be concluded that the techniques of physiological priming, matriosmopriming and matripriming, favored the germination and vigor of the stored crambe seeds.